2009
DOI: 10.1186/1471-2172-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification in milk of a serum amyloid A peptide chemoattractant for B lymphoblasts

Abstract: BackgroundNormal mammary gland contains an extravascular population of B lymphoblasts, precursors of the immunoglobulin plasma cells that play a key role in the passive protection of neonates by secreting immunoglobulins to colostrum and milk. We investigated the presence of chemoattractants in the milk by analysing the chemoattractant activity of various fractions of this secretion. Milk chemoattractants are potentially involved in the recruitment of lymphocytes from the maternal bloodstream in lactating mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…Our observation of SAA3 being exclusive to porcine colostrum is well in line with reports of bovine, equine, and ovine mammary-associated isoforms found in colostrum from healthy animals [49]. Also, previous studies of SAA in pigs have suggested the expression of a mammary-specific SAA isoform [57,58]. Our observations across the pig Pep-tideAtlas clearly suggest a local secretion of the SAA3 isoform to the colostrum and not found in other tissues.…”
Section: Tissue-enriched Expression Of Saa Isoformssupporting
confidence: 91%
See 1 more Smart Citation
“…Our observation of SAA3 being exclusive to porcine colostrum is well in line with reports of bovine, equine, and ovine mammary-associated isoforms found in colostrum from healthy animals [49]. Also, previous studies of SAA in pigs have suggested the expression of a mammary-specific SAA isoform [57,58]. Our observations across the pig Pep-tideAtlas clearly suggest a local secretion of the SAA3 isoform to the colostrum and not found in other tissues.…”
Section: Tissue-enriched Expression Of Saa Isoformssupporting
confidence: 91%
“…This observation is interesting in the light that the pig mammary gland related SAA isoform has been observed to increase during pregnancy, peaking at day 15 of lactation . Also, a specific peptide from SAA3 (DMREANYKNSDKYFHARGNYDAA) was found to act as a chemoattractant for immune cells , indicating that the mammary‐associated isoform of SAA3 may have an important biological role in host response against pathogens, both in the mammary gland and in the gut of the young piglet upon uptake of milk and colostrum proteins.…”
Section: Resultsmentioning
confidence: 87%
“…High levels of SAA have been related to states of inflammation in the mammary gland 37 . However, studies in pigs in healthy lactating mammary glands showed an increase of this gene’s mRNA in the second half of lactation, providing evidence that this peptide could play a physiological role in the normal mammary gland, stimulating neonatal gut immune responses 38 .…”
Section: Resultsmentioning
confidence: 99%
“…There was an abrupt upregulation of SAA2 (serum amyloid A-2 protein) [FC = 3039.23] at 1d postpartum. This isoform is considered the most predominant member of the SAA family expressed in the swine mammary gland [ 70 ]. Rodriguez et al [ 70 ] reported that SAA mRNA production in swine increased during lactation and stimulates the neonatal immune response by enhancing the recruitment of mucosal gut B lymphoblasts and potentially influencing Ig concentrations.…”
Section: Discussionmentioning
confidence: 99%